Musicoterapia e o cuidado ao cuidador de idoso com Alzheimer: um estudo de caso - Santos, Elvira Alves dos (2018)
Population aging has been growing around the world in the last decades, with new demands and challenges emerging for society due to the incidence and prevalence of chronic degenerative diseases, while simultaneously being more of a chronic condition, increasing the risk of complications. As a result of these complications that lead the elderly to a process of dependency, it becomes necessary to have someone who assumes the integral care, a role that is usually attributed to a family member, thus constituting the family caregiver. Due to daily tasks, the life of the family caregiver undergoes a series of changes that directly influence their quality of life, which can trigger an increase in levels of anxiety, stress and depression. Music Therapy can act as a non-medicament and complementary treatment modality, taking a bio-psycho-socio-spiritual approach. The present research deals with a case study, of mixed method, with a phenomenological look for the process and an evaluation before-after for the quantitative data. The aim of this study was to evaluate the effects of Music Therapy on the quality of life and levels of anxiety and depression of family caregivers of patients with Alzheimer's disease (AD), as well as their contribution to the development of resilience and coping strategies. A field study was conducted with a closed group composed of two caregivers, with ages of 50 and 60 years old. Twelve sessions of Music Therapy were conducted, which took place every week, lasting sixty minutes each, initially at a Rehabilitation Center in Goiânia, followed by home visits. Before and after the music therapy process, the WHOQOL-BREF (The World Health Organization Instrument for Quality of Life Bref), BDI (Beck Inventory of Depression) and BAI (Beck Anxiety Inventory) evaluation instruments were applied. The results showed an improvement in the levels of depression and anxiety, considering the absolute values of the scores. Regarding the WHOQOL-BREF, there was no improvement, although the participants affirm that they are in the process of improving the quality of life. Qualitative data revealed meanings and meanings of caring and being cared for, as well as the emergence of existing conflicts that, during the music therapy process, were worked on. It is concluded that music therapy, through the musical experiences experienced during the process, mainly music composition, promoted self-expression, improved self-image and greater access to self-knowledge, contributing to the development of resilience and coping strategies, in addition to the other aspects mentioned.